CYCLIC AMP METABOLISM AND ADENYLATE CYCLASE CONCENTRATION IN PATIENTS WITH ADVANCED HEPATIC CIRRHOSIS - Francavilla, Antonio (1978)
Glucagon was tested for its effect on plasma adenosine 3′,5′-cyclic monophosphate (cyclic AMP), insulin, and glucose in healthy subjects and in patients with advanced cirrhosis of the liver. In the normal subjects, intravenous infusion of glucagon caused a significant increase in plasma cyclic AMP, glucose, and insulin. In advanced cirrhotics, plasma cyclic AMP, glucose, and insulin did not increase. Adenylate cyclase concentration was measured in liver tissue from end stage cirrhotic patients and from brain-dead organ donors whose cardiovascular function was maintained in a stable state. Basal and total adenylate cyclase concentration were not different in the two groups. Adenylate cyclase from the livers of advanced cirrhotics was, however, significantly less responsive to glucagon stimulation than was that from donor livers. Hepatocytes in advanced cirrhosis have abnormal metabolic behavior characterized by abnormal adenylate cyclase-cyclic AMP response to hormonal stimulation.